Detrimental effects of rat mesenchymal stromal cell pre-treatment in a model of acute kidney rejection - Seifert, Martina; Stolk, Meaghan; Polenz, Dietrich; Volk, Hans-Dieter (Frontiers in Immunology, 2012)
Mesenchymal stromal cells (MSC) have shown immunomodulatory and tissue repair potential including partial tolerance induction by pre-treatment of donor-specific cells in a rat heart transplantation model. Very recently, we could show that autologous MSC attenuated ischemia reperfusion injury in a highly mismatched donor-recipient rat kidney transplant model. Therefore, we investigated donor-specific MSC pre-treatment in this rat kidney transplantation model to study whether graft function could be improved, or if tolerance could be induced. Donor- and recipient-type MSC or PBS as a control were injected i.v. four days before kidney transplantation. Mycophenolate mofetil (MMF) immunosuppression (20 mg/kg body weight) was applied for 7 days. Kidney grafts and spleens were harvested between days 8-10 and analyzed by quantitative RT-PCR and immunohistology. In addition, creatinine levels in the blood were measured and serum was screened for the presence of donor-specific antibodies. Surprisingly, application of both donor- and recipient-specific MSC resulted in enhanced humoral immune responses verified by intragraft B cell infiltration and complement factor C4d deposits. Moreover, signs of inflammation and rejection were generally enhanced in both MSC-treated groups relative to PBS control group. Additionally, pre-treatment with donor-specific MSC significantly enhanced the level of donor-specific antibody formation when compared with PBS- or recipient-MSC-treated groups. Pre-treatment with both MSC types resulted in a higher degree of kidney cortex tissue damage and elevated creatinine levels at the time point of rejection. Thus, MSC pre-sensitization in this model impairs the allograft outcome. Our data from this pre-clinical kidney transplantation model indicate that pre-operative MSC administration may not be optimal in kidney transplantation and caution must be exerted before moving forward with clinical studies in order to avoid adverse effects.